2014
DOI: 10.1016/j.worlddev.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Discrimination in Lima, Peru: Evidence from a Field Experiment

Abstract: Latin America is seen as a highly discriminatory society. However, such a common belief appears not to be based on strong empirical evidence (Chong and Ñopo, 2007). This paper exploits novel experimental data gathered to identify the existence of discrimination in the labor market of Lima, Peru, a fast-growing country where much anecdotal evidence suggests the presence of discriminatory practices at many instances of daily life. Focusing on two dimensions, sex (female/male) and surnames (indigenous/white), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 21 publications
1
34
0
2
Order By: Relevance
“…In that sense, our study builds upon the work by Galarza and Yamada (2012), and expands the analysis by López et al (2013) and Ruffle and Shtudiner (2010). Our results provide novel information about the extent of discrimination that can be attributed to each of the three dimensions mentioned earlier.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In that sense, our study builds upon the work by Galarza and Yamada (2012), and expands the analysis by López et al (2013) and Ruffle and Shtudiner (2010). Our results provide novel information about the extent of discrimination that can be attributed to each of the three dimensions mentioned earlier.…”
Section: Introductionsupporting
confidence: 65%
“…However, such an ideal result this does not always hold in reality, as reported by Galarza and Yamada (2012) for the case of Lima. Using an experimental methodology, the authors found that a white person receives almost twice as many callbacks as a Quechua person with similar human capital, and that male candidates are preferred to females.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results suggest that randomization was successful. Table 2 lists callback statistics and shows that the average callback rate is 22%, which is significantly higher than 3-10% found in prior studies (e.g., Bertrand and Mullainathan 2004;Kroft et al 2013;Lahey 2008;Oreopoulos 2011;Galarza and Yamada 2014). About 72% of employers did not call back any applicants, 13% call back one of the two applicants, and 15% call back both applicants.…”
mentioning
confidence: 79%
“…Second, it helps better understand heterogeneous effects by occupation, employer, and foreign country where experience was accumulated. It also contributes to a growing list of labor market audit studies conducted in developing country settings (e.g., Galarza and Yamada 2014;Banerjee et al 2009;Bóo et al 2013).…”
mentioning
confidence: 95%